A Cobalt‐Free Li(Li0.16Ni0.19Fe0.18Mn0.46)O2 Cathode for Lithium‐Ion Batteries with Anionic Redox Reactions. Issue 6 (25th February 2019) - Cheng, Xiaolu; Wei, Hezhuan; Hao, Weijian; Li, Huiyu; Si, Huinan; An, Shengli; Zhu, Wentao; Jia, Guixiao; Qiu, Xinping
Abstract: Lithium‐rich, Mn‐based layered oxides Li2 MnO3 ‐LiMO2 (M=Ni, Co) have been considered as promising cathode candidates owing to their high capacity. However, the resources shortage and high price of cobalt make it imperious to substitute cobalt with other high‐abundance elements. Here, we synthesized a low‐cost, cobalt‐free, Fe‐substituted oxide material, Li(Li0.16 Ni0.19 Fe0.18 Mn0.46 )O2 . It exhibited a high reversible capacity of 169.2 mAh g −1 after 100 cycles and maintained an extraordinarily high discharge potential during cycling. X‐ray photoelectron spectroscopy and DFT calculations revealed that super iron Fe IV exists in the delithiated state, and oxygen participates in the redox reaction in addition to the Ni 2+ /Ni 4+ and Fe 3+ /Fe 4+ redox couples. The anionic oxidation preferentially occurred on oxygen with a Li−O−Li configuration and with oxidized Fe and Ni coordination. Abstract : Cheap and Cobalt‐free ! An Fe‐substituted cathode material for lithium‐ion batteries is developed. The cathodes exhibit a high reversible capacity and maintains an extraordinarily high discharge potential after cycling. XPS and DFT calculations indicate that super iron Fe IV ion exists in the delithiated state. In addition to Ni and Fe, oxygen also participates in the redox reaction during (de)lithiation.